José Ramos-Horta [Indonesia, President of East Timor] - Ramos-Horta, José (Institutional Knowledge at Singapore Management University, 2015)
Having sent to the UN (United Nations) to advocate for independence of Timor-Leste as a young man, José Ramos-Horta have learned much about international hypocrisy. The 1996 Nobel Peace Prize recipient and former President recalled the helpful lessons he acquired from Singapore, his pursuit of peace with Indonesia after the collapse of the Suharto regime, and his take on moral leadership.